Correlation of echocardiographic and angiographic measurements of the pulmonary valve annulus in pulmonary stenosis. Issue 2 (3rd March 2014) - Chubb, H.; Ward, A.; Worme, A.; Qureshi, S.A.; Rosenthal, E.; Krasemann, T.
<x xml:space="preserve">Abstract</x> Objectives The pulmonary valve (PV) annulus is routinely measured angiographically in PV stenosis prior to balloon dilation. We sought to establish whether this radiation exposure is justified, or whether echocardiographic measurements prior to the procedure are sufficient to guide balloon selection. Background Previous studies have found a strong correlation between echocardiographic and angiographic measurements of the PV annulus. However, error of measurement and its implication for procedural practice has not been explored. Methods A total of 90 procedures in 84 patients were analyzed, at a median age 7.6 months (range 1 day to 14.2 years). The contemporaneous echocardiographic and angiographic measurements were recorded, and the original echocardiograms were re‐measured in the 72 available cases by two independent reviewers. Results There was a good correlation between the two measurement methods (R2 = 0.87). However, the echocardiographic PV measurements were smaller on average, with a significant variation in that discrepancy (mean ratio 0.941 (±0.16)). There was no significant reduction in error if extreme measurements (PV annulus z‐score <−3) were excluded (P = 0.09), or if the reviewed echocardiographic measurements were used (P = 0.58). Conclusions There is an unacceptable discrepancy between the measurement techniques: 95% of patients are predicted to have an echocardiographic measurement error between −37% and +26%. Therefore, there is no correction factor that could be employed to allow safe selection of balloon size, and balloon pulmonary valvoplasty without angiographic PV measurement cannot be advocated. © 2014 Wiley Periodicals, Inc.